Pengaruh ekstrak buah naga daging merah (Hylocereus polyrhizus) terhadap berat badan, indeks fagositosis makrofag dan produksi nitrit oksida makrofag (Studi pada mencit BALB/c yang diinfeksi Salmonella typhimurium) - Kusdalinah, Kusdalinah; Johan, Andrew; Wijayahadi, Noor (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2014)
Background: Salmonella typhimurium has ability to avoid the phagosome and escape from the trap-free in cytoplasm.Macrophage was activated to phagocyte microbe and produced microbicidal agent nitric oxide (NO).Polyphenolic compounds are proved as an immunomodulatory agent.Hylocereus polyrhizus contains high level of polyphenols and thus increases appetite.Objective: Proving the effects various doses (6 mg, 12 mg, and 24 mg/20 g miceâ€™s weight) of Hylocereus polyrhizus extract to increase weight, increase macrophage phagocytosis and NO production of macrophage.Methods:True experiment research for fourteen day on males BALB/c mice, post-test only controlled group design.The treatment groups wereÂ  a dose of 6 mg/day (X1), 12 mg/day (X2), and 24 mg/day (X3), whereas the control group (K) was not given the extract of Hylocereus polyrhizus.All treatment and control groups were infected by Salmonella typhimurium intraperitoneally 105 CFU in tenth day.Results: Weight in the treatment group was higher than the control group (p=0.037). Index of macrophage phagocytosis was higher in the treatment group compared to the control group but it was not significant (p=0.154). Macrophage NO production was higher in the treatment group compared to the control group but was not significant (p=0.332).Conclusion: Weight increased significantly.Increasing of macrophage phagocytosis index and macrophage NO production were not significant.